The limitations of patient-centered care: The case of early long-acting reversible contraception (LARC) removal. (January 2022) - Manzer, Jamie L.; Bell, Ann V.
Abstract: Patient-centered care (PCC) is frequently recommended to improve healthcare outcomes in the United States. Despite its purported benefits, little research explores how and to what extent providers implement this model in their care. We examine such processes through the case of contraception, specifically, "early" removals of long-acting reversible contraception (LARC). In-depth interviews with 51 healthcare providers reveal that while providers describe embracing patient-centeredness when considering patients' early LARC removal requests, their implementation ironically sidelines patient preferences and needs. Rather than be responsive to patients' requests, all providers in the study resist early LARC removal by: withholding information about self-removal of intrauterine devices (IUDs); negotiating with patients to keep their device longer; setting subjective timelines to prolong LARC use; and/or engaging in delay tactics to wear down patients' resolve for removal. Furthermore, beyond simply resisting LARC removal requests using these strategies, providers purposively employ tenets of PCC to sway patients away from removal. In other words, providers utilize PCC as a means to undermine it. Understanding how providers implement patient-centered care reveals the challenges to doing so, even in cases like early LARC removal where providers indicate patient-centeredness is a priority. It also elucidates the need for enhanced training, specificity, and institutionalization around patient-centered models of care; informs interventions that promote LARC use among patients; as well as offers opportunities for improving patient-provider exchanges generally. Highlights: Patient-centered care (PCC) is often recommended to improve healthcare outcomes in the U.S. As currently implemented, PCC can contribute to healthcare inequalities. Despite PCC, healthcare providers resist patients' requests for early IUD and implant removals. Providers use PCC principles to deny and delay these removals; ultimately undermining PCC. Enhanced provider training, term specificity, and institutionalization around PCC is needed.